Financial barriers in achieving CIDB IBS Roadmap in Malaysia private sector construction industry - Lim, Desmond Eng Hong; Chan, Siew Chong (INTI International University, 2018)
Industrialized Building System (IBS) was originally introduced by Malaysian government to solve the problems of providing affordable housing for the people, and later this construction method was further under studied to cover other possible areas to resolve other construction problems in Malaysia. Compared with other countries such as Japan and Singapore, the implementation stage of IBS in this country is rather low which may due to Financial Barrier that limits its utility. This research is aimed to investigate the extent of Finance Barrier which cause the private sector from implementing IBS and achieving the targets set by CIDB in its Roadmap. The effectiveness of the policy, its related recommendations and strategies to ensure the ability of Roadmap to resolve the construction problems were also under studied. Data and information obtained from questionnaire distributed to 66 respondents from private sector were analyzed using Frequency Distribution Analysis Method. The findings of the research show that Financial Barrier is indeed a critical factor that limit the IBS application in achieving the targets set by IBS Roadmap, and thus, it is urgently required the respective parties, especially from CIDB to prioritize its strategies that effectively to resolve the financial problems and also further promote the potential of utilizing IBS construction method in Malaysian construction industry.